Brides and doom : gender, property, and power in medieval German women's epic - Frakes, Jerold C. (University of Pennsylvania Press, 1994)
Jerold C. Frakes approaches the Nibelungenlied, the Klage, and the Kudrun, epic poems central to the Middle High German tradition, through a set of literary, economic, ad sociological interpretations, informed by a broad range of contemporary feminist scholarship.
Keywords: Epic poetry, German -- History and criticism.; German poetry -- Middle High German, 1050-1500 -- History and criticism.; Women -- Germany -- History -- Middle Ages, 500-1500.; Feminism and literature -- Germany -- History.; Women and literature -- Germany -- History.; Civilization, Medieval, in literature.; Power (Social sciences) in literature.; Sex role in literature.; Property in literature.; Poésie allemande -- 1050-1500 (Moyen haut allemand) -- Histoire et critique.; Femmes -- Allemagne -- Histoire -- 500-1500 (Moyen Âge); Femmes et littérature -- Allemagne -- Histoire.; Civilisation médiévale dans la littérature.; Pouvoir (Sciences sociales) dans la littérature.; Rôle selon le sexe dans la littérature.; Poésie épique allemande -- Histoire et critique.; POETRY -- Continental European.; LITERARY COLLECTIONS -- Medieval.; Civilization, Medieval, in literature; Epic poetry, German; Feminism and literature; German poetry -- Middle High German; Power (Social sciences) in literature; Property in literature; Sex role in literature; Women and literature; Women -- Middle Ages; Germany; 500-1500; Criticism, interpretation, etc.; History